2020
DOI: 10.1002/anie.201916592
|View full text |Cite
|
Sign up to set email alerts
|

Oriented (Local) Electric Fields Drive the Millionfold Enhancement of the H‐Abstraction Catalysis Observed for Synthetic Metalloenzyme Analogues

Abstract: This contribution follows the recent remarkable catalysis observed by Groves et al. in hydrogen‐abstraction reactions by a) an oxoferryl porphyrin radical‐cation complex [Por⋅+FeIV(O)Lax] and b) a hydroxoiron porphyrazine ferric complex [PyPzFeIII(OH)Lax], both of which involve positively charged substituents on the outer circumference of the respective macrocyclic ligands. These charge‐coronated complexes are analogues of the biologically important Compound I (Cpd I) and synthetic hydroxoferric species, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 40 publications
1
63
0
Order By: Relevance
“…We investigated alternative mechanistic proposals, i.e., C−H or N−H hydrogen abstraction, and explored the effects of long‐range interactions. We also explored the effects of applying an external electric field (EEF) on the reaction mechanism and product selectivity [28b–g] . Comparison of the results for the RDM activity of KDM4E with the KDM activity of KDM4A imply both proceed via ferryl mediated C−H abstraction, but that there are differences in the interactions leading to the formation of intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated alternative mechanistic proposals, i.e., C−H or N−H hydrogen abstraction, and explored the effects of long‐range interactions. We also explored the effects of applying an external electric field (EEF) on the reaction mechanism and product selectivity [28b–g] . Comparison of the results for the RDM activity of KDM4E with the KDM activity of KDM4A imply both proceed via ferryl mediated C−H abstraction, but that there are differences in the interactions leading to the formation of intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…Mayer reported this same complex to be a fast and efficient catalyst for the oxygen reduction reaction (ORR). 26 The Shaik group recently published a computational study 27 characterizing two Fe/porphyrin complexes that contain cationic pyridinium residues in the secondary coordination sphere. Groves, in his original report on these complexes, showed that they undergo unprecedentedly fast C–H activation kinetics ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“… 28,29 Shaik's study was able to reproduce activation energies from the experimental data through replacement of the charged functional groups with external oriented electrostatic fields, thereby implicating the catalytic effect as being almost purely electrostatic in origin. 27 …”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, artificially designed electric fields have also been utilized to mediate non‐redox reactions through, for example, the electrode/electrolyte interface, [3] a voltage‐biased STM tip, [4] and the active site under the electric field possibly created by charged functional groups [5] or catalysts [6] . From a theoretical point of view, a large number of studies have been dedicated to the understanding and prediction of the effect of an oriented external electric field (OEEF) on various chemical transformations [7] such as C−H bond activation reactions, [6a–c, 7a–c] Diels–Alder reactions, [5e, 6d, 7d,e] methyl transfer reactions, [7f] electrophilic aromatic substitution reactions, [7g] nucleophilic substitutions of halogen‐bond complexes, [7h] and oxidative addition reactions [7i] …”
Section: Introductionmentioning
confidence: 99%